In Memory of Assoc. Prof. Dato’ Dr. Vellayan Subramaniam: former lecturer of Faculty of Pharmacy UiTM / Mizaton Hazizul Hasan - Hasan, Mizaton Hazizul (Faculty of Pharmacy, 2024)
“Professor, Professor”, his booming voice greeted me every time we crossed paths, smiling ear-toear with his elephant-printed tie. A man with a BIG personality, he was. We mourn his passing, yet we will always remember his contributions to veterinary medicine and wildlife conservation. He would try to preserve as many roadkills as possible from his drive to work in Puncak Alam. “The staff need to learn”, he said. Always a teacher and a true educator.